2019
DOI: 10.1111/1756-185x.13720
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of the unsupported upper‐limb exercise test in individuals with rheumatoid arthritis

Abstract: Background Rheumatoid arthritis (RA) is a chronic disease which affects the performance of the upper extremities. There is no method to evaluate the specific upper extremity endurance of individuals with this disease. The unsupported upper‐limb exercise test (UULEX) is a performance test that evaluates upper extremity performance (functionality and endurance). Aim The aim of this study was to examine the reliability and validity of UULEX and the minimal detectable change (MDC) in individuals with RA. Methods a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 24 publications
1
13
0
1
Order By: Relevance
“…Higher test scores were correlated with better shoulder girdle muscle performance and lower disability levels in patients with CNP. The UULEX was developed on COPD patients (Takahashi et al, 2003), and its validity and reliability studies were conducted on patients with RA (Cetin et al, 2019) and with healthy individuals (Lima et al, 2018). Prior studies have shown that the UULEX had high test-retest reliability in different groups (Cetin et al, 2019; Lima et al, 2018; Oliveira et al, 2018; Takahashi et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher test scores were correlated with better shoulder girdle muscle performance and lower disability levels in patients with CNP. The UULEX was developed on COPD patients (Takahashi et al, 2003), and its validity and reliability studies were conducted on patients with RA (Cetin et al, 2019) and with healthy individuals (Lima et al, 2018). Prior studies have shown that the UULEX had high test-retest reliability in different groups (Cetin et al, 2019; Lima et al, 2018; Oliveira et al, 2018; Takahashi et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Participants in this study were patients, aged 18–65, years with neck pain lasting at least three months due to such causes such as cervical strain or sprain, cervical disc lesions, cervical spondylosis, facet joint dysfunction, and myofascial pain syndrome (Misailidou et al, 2010). Participant exclusion criteria were: (a) the presence of additional diseases that could affect UE and hand functions, (b) having undergone UE or cervical region surgery, (c) having experienced cervical radiculopathy, rheumatic disease, or presence of neurological symptoms, (d) activity-related neck pain severity below 3, according to the Visual Analog Scale, (e) having acute or chronic respiratory disease and/or cardiac disease, (f) showing a problem in perceiving verbal commands, and (g) pregnancy (Takahashi et al, 2003; Cetin et al, 2019; Marques et al, 2020; Lima et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…The first report of UULEX in literature was to assess upper extremity functional level in individuals with chronic obstructive pulmonary disease (17,18). Although UULEX has been shown to be a valid and reliable test for healthy and rheumatoid individuals (26)(27)(28), there are no studies in literature illustrating that this test is valid and reliable for diabetic individuals. This can be considered a limitation of this study.…”
Section: Discussionmentioning
confidence: 99%
“…(10) We find it interesting that the UULEX test has recently been validated for patients with rheumatoid arthritis. (11) The mean UULEX completion time was 8.26 min (95% CI: 2.30-11.00), which is below the normative value of 12.50 min (95% CI: 9.48-15.00) for women in the 51-to 60-year age group, (7) corresponding to 66% of the predicted value. Although these are only illustrative examples, because the samples of patients were in countries not included in the development of the normative values, this analysis is a way of showing their applicability not only in research but also in clinical practice.…”
mentioning
confidence: 80%